Histopathological correlates of haemorrhagic lesions on ex vivo magnetic resonance imaging in immunized Alzheimer's disease cases. Issue 1 (3rd February 2022) - Scherlek, Ashley A.; Kozberg, Mariel G.; Nicoll, James A. R.; Perosa, Valentina; Freeze, Whitney M.; van der Weerd, Louise; Bacskai, Brian J.; Greenberg, Steven M.; Frosch, Matthew P.; Boche, Delphine; van Veluw, Susanne J.
Abstract: Haemorrhagic amyloid-related imaging abnormalities on MRI are frequently observed adverse events in the context of amyloid β immunotherapy trials in patients with Alzheimer's disease. The underlying histopathology and pathophysiological mechanisms of haemorrhagic amyloid-related imaging abnormalities remain largely unknown, although coexisting cerebral amyloid angiopathy may play a key role. Here, we used ex vivo MRI in cases that underwent amyloid β immunotherapy during life to screen for haemorrhagic lesions and assess underlying tissue and vascular alterations. We hypothesized that these lesions would be associated with severe cerebral amyloid angiopathy. Ten cases were selected from the long-term follow-up study of patients who enrolled in the first clinical trial of active amyloid β immunization with AN1792 for Alzheimer's disease. Eleven matched non-immunized Alzheimer's disease cases from an independent brain brank were used as 'controls'. Formalin-fixed occipital brain slices were imaged at 7 T MRI to screen for haemorrhagic lesions (i.e. microbleeds and cortical superficial siderosis). Samples with and without haemorrhagic lesions were cut and stained. Artificial intelligence-assisted quantification of amyloid β plaque area, cortical and leptomeningeal cerebral amyloid angiopathy area, the density of iron and calcium positive cells and reactive astrocytes and activated microglia was performed. On ex vivo MRI, cortical superficial siderosis was observed in 5/10 immunized Alzheimer's disease cases compared with 1/11 control Alzheimer's disease cases ( κ = 0.5). On histopathology, these areas revealed iron and calcium positive deposits in the cortex. Within the immunized Alzheimer's disease group, areas with siderosis on MRI revealed greater leptomeningeal cerebral amyloid angiopathy and concentric splitting of the vessel walls compared with areas without siderosis. Moreover, greater density of iron-positive cells in the cortex was associated with lower amyloid β plaque area and a trend towards increased post-vaccination antibody titres. This work highlights the use of ex vivo MRI to investigate the neuropathological correlates of haemorrhagic lesions observed in the context of amyloid β immunotherapy. These findings suggest a possible role for cerebral amyloid angiopathy in the formation of haemorrhagic amyloid-related imaging abnormalities, awaiting confirmation in future studies that include brain tissue of patients who received passive immunotherapy against amyloid β with available in vivo MRI during life. Abstract : Scherlek et al. report haemorrhagic lesions on ex vivo MRI in brain tissue samples of Alzheimer's disease patients who received anti-amyloid immunotherapy during life. These lesions were associated with severe leptomeningeal cerebral amyloid angiopathy, suggesting a possible role for cerebral amyloid angiopathy in the formation of haemorrhagic amyloid-related imaging abnormalities. Graphical Abstract: